2019
DOI: 10.21203/rs.2.14008/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Women’s knowledge and attitudes toward cervical cancer and cervical cancer screening in Zanzibar, Tanzania: a cross- sectional study

Abstract: Background: Cervical cancer is the most common cancer and the leading cause of cancer death among women in Tanzania. Knowledge and willingness of cervical cancer screening are important determinants of prevention services. This study aimed to describe women's awareness about cervical cancer and to explore the attitudes, acceptability and barriers toward cervical cancer screening in Zanzibar, Tanzania, in order to help organizing the forthcoming China-Zanzibar cervical cancer screening program. Methods: A cross… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
1
2
Order By: Relevance
“…Education level and employment appear to play no role in the knowledge about cervical cancer in our study. These results are not consistent with other studies in SSA [ 7 , 22 , 30 , 31 ]. Also, no correlation was found between multiparous and cervical cancer knowledge, as has been reported in previous studies from Tanzania [ 22 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Education level and employment appear to play no role in the knowledge about cervical cancer in our study. These results are not consistent with other studies in SSA [ 7 , 22 , 30 , 31 ]. Also, no correlation was found between multiparous and cervical cancer knowledge, as has been reported in previous studies from Tanzania [ 22 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This is possible because women who have health insurance may have better health-seeking behavior and have had more interaction with health facilities. These findings are in tandem with results from a study from Zanzibar [ 30 ]. Another study from Zimbabwe found that women with a higher income, and who had more contact with the health care system had better cervical cancer knowledge [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Although attending college or university showed a higher likelihood of undergoing screening in other studies, 24,25 our study showed no association between education and the likelihood of a woman to undergo screening. This trend can be attributed to the fact that there is easy access to education in Kazakhstan.…”
Section: Discussioncontrasting
confidence: 75%
“…The data shows that public awareness especially women of childbearing age to perform VIA is still low, whereas the Government has encouraged healthy lifestyle and early detection. This problem occurs because their knowledge of cervical cancer is lacking, felt ashamed, felt no symptoms of cervical cancer, and felt no need to be checked (Weng, Jiang, Haji, Nondo, & Zhou, 2020). Educational influence is inevitable for such case, intended to woman of childbearing age on VIA test with Emo Demo (Emotional Demonstration) method.…”
Section: Introductionmentioning
confidence: 99%